Piezoelectric Trasducer Based Micro Energy Generator Design for Application in Ceramics - Mayantasari, Menasita; Al-Zairi, Achmad; Rahastama, Swastya (SPECTA Journal of Technology, 2023)
The rapid development of technology causes humans to provide a large amount of energy, especially electrical energy. One of the new renewable energy sources that is still under development is a piezoelectric-based energy harvester. Piezoelectric itself is a material that has an electric polarizing effect that occurs in certain materials when the material is given a mechanical stress. The potential difference measured across the piezoelectric material is proportional to the applied pressure. This study aims to examine the prototype of a piezoelectric-based micro energy generator using different loadings on ceramics. This research was carried out by making a prototype on a 30x30 cm2 ceramic, and using a piezoelectric in the form of a PZT type. The method used in this research is measuring the voltage of each configuration variation in the piezoelectric circuit. Retrieval of stress data was done by dropping a load of 3 kg, 6 kg and 9 kg for each variation to be tested. The distance between the piezoelectric position and the center of mass affected the resulting voltage, each additional load would cause an increase in voltage, and a series circuit produces a greater voltage than a parallel circuit